A breach of tradition during socialism : the case of water syndicates in Bulgaria - Insa Theesfeld; Ivan Boevski (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2003)
During the post-socialist transition period, the Bulgarian irrigation facilities deteriorated to a large extent and no longer meet the needs of the new landowner and agricultural production structure. The Bulgarian government therefore enacted two new laws to encourage collective action and to establish water user associations in order to achieve sustainable water management. In this article, we will question the frequent argument that water user associations could easily be established in Bulgaria, because they are rooted in the water syndicates. Empirical findings from village case studies reveal that limited collective memory exists today about former water syndicates? rules-in-use and patterns of action. We will explain this breach of tradition by the migration from villages to cities, the suppression of precommunist so-called capitalist behaviour, and the length of the communist period. Moreover, the analysis of the historical cooperative development in Bulgaria shows that the water syndicates were enforced by a top-down approach and did not have much in common with the classic cooperative principles.
Keywords: 330; Bewässerung; Kartell; Bulgarien